Investigação de surto de Diarréia: um Estudo de Coorte Retrospectiva em Campinas, São Paulo, Setembro de 2004 - V. S. César, Maria Lúcia V. S. César; de P. Eduardo, Maria Bernadete; Y. J. da Silveira, Naoko; Rocha Martins, Bruno; Costa Silva, Carolina; Rodrigues, Michelle Maria; S. T. Timenetsky, Maria do Carmo (BEPA. Boletim Epidemiológico Paulista, 2005)